The services on Land and Survey Department to the public / Feiionna Mili and Nur Asyiken Ahmad - Mili, Feiionna; Ahmad, Nur Asyiken (2017)
The purpose of this study to identify what are the efficient services provided land at Land and Survey Department in Kota Kinabalu. The services are focus on land section. This study was done using self-developed questionnaire that involved 100 respondents who use the services on the Land and Survey Department. The findings are, the efficient services are on the procedure of land surveying services and the inefficient services are on the procedure of application land. It is concluded that the efficient services are on the land surveying services.